Oferta pública inicial y underpricing en el mercado de capitales mexicano - Villarreal, Cuauhtemoc (2013)
Companies decide to go public for several reasons, among them we can mention liquidity issues, obtaining financing, and lower capital cost. Once the company was valued and the financial intermediary sets a price for the shares, the companies come to the market to a particular offer price. At the end of the first day of trading, the company presents a closing price. In the international context, the tendency for the initial public offering (IPO) is having a closing price greater than the issued. This is known under the term underpricing. The degree of underpricing varies across markets. Studies in the United States, found 36% yields, while China has had an underpricing of 298% and 46% in Germany. This research will analyze the IPO’s issued in Mexico in the period from 2000 to May 2012, seeking to determine if a situation of underpricing in IPO’s exists in the Mexican market. DOI:  10.1016/S2077-1886(13)70034-9